2011
DOI: 10.1007/s11745-011-3580-y
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis is Associated with Markedly Increased Triglycerides and Small Dense Low‐Density Lipoprotein and Decreased High‐Density Lipoprotein

Abstract: The objective of the present study was to evaluate the effects of acute infection with Leptospira interrogans on lipids, lipoproteins and associated enzymes. Fasting serum levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglycerides (TG), apolipoproteins (apo) A-Ι, B, E, C-II, C-III and lipoprotein (a) [Lp(a)] were determined in patients with Leptospirosis on diagnosis and 4 months after recovery as well as in age- and sex-matched co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 42 publications
3
23
0
3
Order By: Relevance
“…We have previously shown that the reduction in LDL-C seen in patients with brucellosis, EBV infection and leptospirosis was associated with the increased levels of IL-6 and TNFa [3,4,8]. We have previously shown that the reduction in LDL-C seen in patients with brucellosis, EBV infection and leptospirosis was associated with the increased levels of IL-6 and TNFa [3,4,8].…”
Section: Discussionmentioning
confidence: 98%
“…We have previously shown that the reduction in LDL-C seen in patients with brucellosis, EBV infection and leptospirosis was associated with the increased levels of IL-6 and TNFa [3,4,8]. We have previously shown that the reduction in LDL-C seen in patients with brucellosis, EBV infection and leptospirosis was associated with the increased levels of IL-6 and TNFa [3,4,8].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, a relationship between HDL and leptospiral pathogenesis has also been identified; serum levels of HDL are reduced during leptospiral infection in guinea pigs and humans (43,44). Moreover, a recent study showed that levels of ApoA-I precursor were reduced up to 3-fold in the sera of human leptospirosis patients (45).…”
Section: Discussionmentioning
confidence: 99%
“…Negative-control mice were injected with PBS. Two weeks after each immunization, the mice were bled from the retro-orbital plexus and the pooled sera were analysed by ELISA (Gazi et al, 2011) for determination of antibody titre.…”
Section: Methodsmentioning
confidence: 99%